Scintigrafisk undersökning av esofagusmotilitet hos häst - Almerén, Johanna (2008)
Scintigraphic examination of the esophagus has for some time been the method of choice for the study of motility dysfunction in humans. The method has not yet been described for horses hence the lack of reference values for passage time for a bolus through the esophagus in healthy subjects. The purposes of this study were to measure passage velocity and time for a bolus to pass through the esophagus in healthy subjects, as well as to evaluate the reproducibility of the method. Eight warm-blooded trotters were used in the study. The horses were sedated with a low dose of Acepromazine prior to onset of the study. The esophagus was divided into five sections by radioactive markers and two bolus passages per section were registered with a gamma camera. Three different passage times were calculated: the time for passage from the larynx to the cardia, through the cardia and from the larynx into the stomach. The velocities through the five different sections of the esophagus were calculated using the length of the esophagus and the passage times. The average speed in the cervical portion of the esophagus were proximally 40 ± 4.1 centimeter per second and distally 37 ± 6.6 centimeter per second. The velocity decreased as the bolus moved caudally in the esophagus. The passage time from the larynx to the cardia was 4.2 ± 0.6 seconds, through the cardia 2.4 ± 0.6 seconds and the total passage time was 6.6 ± 0.7 seconds. A few horses showed gastroesophageal reflux and retention of the bolus in some of the sections of the esophagus. The coefficient of variation the velocity for the repeated studies of each individual varied between 10 and 30 percent between the esophagus sections. Despite the great variation in reproducibility, we estimate that the method is functional in clinical work, since motility dysfunction in the esophagus is reflected in marked prolongation of the passage time. Some of the advantages with scintigraphic examination are that the method is simple and practical, causes little or no suffering to the patient and exposes the staff for a lesser dose of radiation than ordinary radiography.